Indícios do sistema coeducativo na formação de professores pelas escolas normais durante o regime republicano em São Paulo (1890/1930) - Almeida, Jane Soares De [UNESP] (Setor de Educação da Universidade Federal do Paraná, 2009)
The article analyses the training of teachers by normal schools in Sao Paulo from 1890 to 1931, period guided by the adoption in the school system of ideas of the Republican Enlightenment. According to the spirit of federation that took over the country and the Enlightenment ideas, aligned with the positivism and the liberal conceptions, the public school should be improving and expanding. The normal schools were the ideal institutions for such training and at the same time, indicated that women have all the qualifications to take care of the children education. Attempts to deploy the co-educational system, targeting equal education for the two sexes, proposal which has restrictions on families, educators and the Catholic Church, it caused some discussions that ultimately fall into the void in light of the most pressing educational issues.

O artigo analisa a formação de professores pelas escolas normais em São Paulo no período de 1890 até 1931, época pautada pela adoção no Sistema Escolar do ideário do Iluminismo republicano. De acordo com o espírito de federação que tomou conta do País e as ideias iluministas, alinhadas com o Positivismo e com as concepções liberais, a escola pública devia se aperfeiçoar e expandir. As escolas normais foram as instituições ideais para essa formação e, ao mesmo tempo, indicava-se que as mulheres possuíam todas as qualificações para se encarregarem do ensino de crianças. As tentativas de implantar o sistema coeducativo, visando educação igual para os dois sexos, proposta que sofreu restrições das famílias, dos educadores e da Igreja Católica ocasionaram algumas discussões que acabaram por cair no vazio em vista das questões educacionais mais prementes.
Evidences of the co-educational system in the training of teachers by the normal schools during the republican regime in São Paulo (1890/1930)
Keywords: normal schools; training of teachers; co-education; escolas normais; formação de professores; coeducação